Globalization and the Gender Earnings Gap : Evidence from Sri Lanka and Cambodia - Savchenko, Yevgeniya; Lopez Acevedo, Gladys; Robertson, Raymond (World Bank, Washington, DC, 2017)
Disasters in Bangladesh and protests elsewhere have created an intense debate about the value, particularly to women, of apparel employment in developing countries. This paper focuses on how the forces of globalization, specifically the Multi-Fibre Arrangement (MFA), have affected women's wages in the apparel sector in developing countries. The paper uses household and labor force surveys from Cambodia and Sri Lanka to estimate both apparel wage premiums relative to other industries and the male-female wage gap before and after the end of the MFA. The approach builds on new models that apply traditional trade theory (e.g., the Heckscher-Ohlin and Stolper-Samuelson theorems) to analyze the effect of globalization on gender-based earnings. The authors find large positive wage premiums and a closing of the male-female wage gap during the MFA period, but smaller premiums and a widening wage gap after the end of the MFA. The results suggest that the benefits of apparel exports for women in developing countries remain significant post-MFA. They also model an approach for studying the effects of globalization that differentiates males and females as separate factors. This may be a fruitful alternative to discrimination models or those that analyze the effects of globalization on women in terms of skill. Further research is necessary to identify the potential development effects of post-MFA apparel employment and to thoroughly compare the benefits documented in this paper with the costs that may come with apparel jobs.